2017
DOI: 10.4081/aiua.2017.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HIV virus in the hospital stay and the occurrence of postoperative complications classified according to the Clavien-Dindo classification and in comparison with the Charlson Comorbidity Index in patients subjected to urologic and general surgery operations. Our preliminary results

Abstract: Objectives: From the first time that human immunodeficiency virus (HIV) was discovered, till today both the quality of life and survival expectancy of HIV-infected patients have markedly improved. As the life expectancy of these patients increases due to the use of highly active anti-retroviral therapy (HAART) also increases the number of HIV-positive patient to be subjected to an operation. Different studies have examined the occurrence of complications in this particular group of patients and their possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Future studies, in which pre-mortem medical conditions are thoroughly documented, might consider applying alternative multimoribidity indexes, such as those that provide weights for more serious medical conditions 32,33 and which have been applied in specific contexts, such as HIV research. [34][35][36] Compared to tissues from uninfected individuals, those from HIV-positive individuals exhibit increased DNAmAge in kidney. HIV-1 infection is associated with an increased risk for a number of diseases and medical conditions typically associated with aging, including cardiovascular disease, osteoporosis, several cancers, kidney disease, liver disease, and cognitive decline [37][38][39][40][41][42][43][44][45][46][47][48][49] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies, in which pre-mortem medical conditions are thoroughly documented, might consider applying alternative multimoribidity indexes, such as those that provide weights for more serious medical conditions 32,33 and which have been applied in specific contexts, such as HIV research. [34][35][36] Compared to tissues from uninfected individuals, those from HIV-positive individuals exhibit increased DNAmAge in kidney. HIV-1 infection is associated with an increased risk for a number of diseases and medical conditions typically associated with aging, including cardiovascular disease, osteoporosis, several cancers, kidney disease, liver disease, and cognitive decline [37][38][39][40][41][42][43][44][45][46][47][48][49] .…”
Section: Discussionmentioning
confidence: 99%
“…Future studies, in which pre-mortem medical conditions are thoroughly documented, might consider applying alternative multimoribidity indexes, such as those that provide weights for more serious medical conditions 32,33 and which have been applied in specific contexts, such as HIV research. 34-36…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Some surgeons seem reluctant to operate on HIV-positive patients due to concerns regarding the risk of personal transmission of the virus and poor surgical outcomes. 15,16 This review reported that HIV-positive patients submitted to surgery for DSD have higher complication rates and conflicting data regarding surgical outcomes. No statistical differences in mortality were observed between HIV-negative and HIV-positive patients after degenerative cervical spine surgery.…”
Section: Surgical Cases In Hiv Patientsmentioning
confidence: 99%
“…[10][11][12][13] In spite of this, the incidence of spine surgery for DSD on HIV-positive patients seems to be low (0.23%), although it is not well determined. [14][15][16] The authors conducted a systematic review of clinical studies on surgery for DSD in HIV-positive patients. The main clinical questions to be answered in this review were if HIVpositive patients undergo less spine surgery and if they have poorer outcomes when compared with noninfected patients.…”
Section: Introductionmentioning
confidence: 99%